MEKANISASI PERTANIAN MELALUI INOVASI TRAKTOR BAJAK SAWAH RAKITAN DENGAN PENGGERAK MESIN MOTOR BEKAS - diki triyudi refindo (Inisiasi, 2023)
The agricultural sector is a source of food supplies. One of the problems that farmers often face in agricultural business is that they still use traditional technology so it is less effective. This research aims to innovate a rice plow tractor using an assembly with a used motor engine. Manufacturing is divided into 3 processes, namely the pre-production process, production process and post-production process. The results of the research produced a rice plowing tractor driven by a used motor engine which has been tested and implemented in several rice fields in Wonogiri Regency. The advantages of the "Assembled Tractor with Used Motor Engine" innovation compared to existing tractors are: the price is more affordable for farmers; specifications can be adjusted to suit needs; easy to use and practical; better land yields. The existence of a Tractor Assembled from Used Motorcycle Engines is a transformation for farmers towards farming that is more affordable, effective and environmentally friendly with the function of local products being no less than foreign products.